Comparing housing systems housing performance and housing policy in the United States and Britain - Karn, Valerie Ann; Wolman, Harold (Clarendon Press, 1992)
Unlike other work in the field, this comparative study of housing in the United States and Britain focuses on housing performance. Professor Karn and Professor Wolman begin by identifying and comparing the most important aspects of the performance of housing systems: housing supply and quality, its cost to occupants, equity and distribution, and housing investment and production. In the second part of the book they go on to account for the differences in housing performance that their initial examination reveals. They consider a wide range of factors, including housing institutions, wealth and income, and cultural predisposition. But the main part of their discussion focuses on differences in public policy in Britain and the USA and they examine in detail how these contribute to the success or otherwise of British and American housing systems. Finally the authors examine 'housing policy agendas' in both countries, looking particularly at the extent to which shortcomings in housing performance are recognized as such and included in public policy planning. Their research will make an important and original contribution to the comparative literature of housing studies.
Keywords: Economische aspecten; Habitacao (planejamento); Habitacao (sociologia); Huisvestingsbeleid; Rechtsvergelijking (vorm); Wirtschaft; Housing policy -- Great Britain; Housing policy -- United States; Housing -- Great Britain; Housing -- United States; Wohnungsversorgung; Wohnungspolitik; Großbritannien; USA